2021
DOI: 10.1021/acs.energyfuels.0c04120
|View full text |Cite
|
Sign up to set email alerts
|

Shale Wettability: Data Sets, Challenges, and Outlook

Abstract: The wetting characteristics of shale rocks at representative subsurface conditions remain an area of active debate. A precise characterization of shale wettability is essential for enhanced oil and gas recovery, containment security during CO 2 geo-storage, and flow back efficiency during hydraulic fracturing. While several methods were utilized in the literature to evaluate shale wettability (e.g., contact angle measurements, spontaneous imbibition method ,and NMR method), we here review the recently publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 138 publications
1
41
0
Order By: Relevance
“…Wettability is defined as the attraction of a liquid phase to solid surface and is typically quantified using a contact angle with the solid phase. It is the ability of a liquid to maintain contact with a solid surface and is controlled by the balance between the intermolecular interactions of the adhesive type (liquid to surface) and cohesive type (liquid to liquid). , They concluded that shales are water-wet at in situ conditions. Nikolaev and Kazak reviewed experimental methods, including nuclear magnetic resonance (NMR) and Rock-Eval pyrolysis, to characterize oil and water saturation in organic-rich unconventional reservoirs .…”
Section: Introductionmentioning
confidence: 99%
“…Wettability is defined as the attraction of a liquid phase to solid surface and is typically quantified using a contact angle with the solid phase. It is the ability of a liquid to maintain contact with a solid surface and is controlled by the balance between the intermolecular interactions of the adhesive type (liquid to surface) and cohesive type (liquid to liquid). , They concluded that shales are water-wet at in situ conditions. Nikolaev and Kazak reviewed experimental methods, including nuclear magnetic resonance (NMR) and Rock-Eval pyrolysis, to characterize oil and water saturation in organic-rich unconventional reservoirs .…”
Section: Introductionmentioning
confidence: 99%
“…Preheating of the air and fuel is carried out in particular power plants to achieve this goal [22] [23]. Preheating the air may be accomplished by using renewable energy sources, which will be more ecologically friendly and long-lasting [24] [25]. A gas turbine connected with an air preheating solar field was modeled using TRNSYS and Thermoflex to simulate the system's performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous researches have been done on the pore structure, interphase interaction, and flow mechanisms in macroscale [22][23][24][25][26], mathematical models capable of accurately characterizing the pore deformation, dynamic capillary force phenomenon, and oil-water two-phase transport at the nanopore scale for shale oil are still missing [27][28][29][30][31]. To solve this problem, Gassmann's method is modified to describe the change of pore radius and roughness in the dynamic pressure field for elastic deformation.…”
Section: Introductionmentioning
confidence: 99%